Pengaruh Store Atmosphere, Kualitas Pelayanan dan Social Media Marketing Terhadap Keputusan Pembelian - Ulvi Mardhatillah; Siska Lusia Putri (New Economy, 2026)
This study aims to determine the effect of store atmosphere, service quality and social media marketing on purchasing decisions. The population used in this study were customers who had visited Show Koffie Padang. This study used 100 respondents using the Lemeshow formula as a sampling technique. Hypothesis testing in this study used statistical analysis consisting of validity tests, reliability tests, classical assumption tests (normality tests, multicollinearity tests, and heteroscedasticity tests) using SPSS (Statistics Product and Service Solution) software version 24. The research data came from primary data taken by distributing questionnaires. The results of this study indicate that store atmosphere has a positive and significant effect on purchasing decisions, service quality has an insignificant effect on purchasing decisions while social media marketing has a positive and significant effect on purchasing decisions. Simultaneously all variables, namely store atmosphere, service quality and social media marketing have a significant effect on purchasing decisions for Show Koffie Padang customers.